Surgical technique of total hip arthroplasty: an experience from a tertiary level hospital in India - Gupta, Lokesh; Lal, Mukund; Aggarwal, Vineet; Rathor, Lakshya Prateek (International Journal of Research in Orthopaedics, 2018)
Background: Total hip arthroplasty (THA) is performed for patients with hip pain, which may arise due to a variety of conditions. Methods: An observational study of 20 hip joints presenting to the Department of Orthopedic Surgery, Indira Gandhi Medical College Shimla from December 2008 till December 2010 for THR was done. Laboratory and imaging investigations were performed as per the standard operating protocol of our center. Modified Harris Hip scoring was done for all included patients pre-operatively. A posterolateral approach with posterior dislocation of hip was used in all the patients. Pre-operative and intra-operative details were noted using a pretested semi-structured questionnaire. Data were analysed descriptively and tabulated to draw conclusions. Results: Both sides were operated with equal frequency, while one patient had a bilateral THA. Most common indication of surgery was osteoarthritis secondary to avascular necrosis head of femur (n=16). Pre-operative modified Harris hip score was poor in all 20 hip joints. Duration of surgery ranged from 110 minutes to 190 minutes, mean duration being 139 minutes. Average blood loss during the surgical procedures was about 532 ml with average drainage of about 230 ml. On an average medullary canal flare index of 3.97 was for all the patients. Morphological cortical index averaged at 3.11 and Dorr index at 3.54. Conclusions: Most systems for THA are modular which provide flexibility in dealing with intraoperative anatomical variations. Different types of femoral and acetabular implants are available for use which reflect the different philosophies regarding the techniques involved in THA. Further studies are required to support our findings.